Pendidikan dan Pelatihan (Diklat) Peningkatan Kompetensi Guru-Guru SMP Kabupaten Barru - Muhammad Irfan; Afdhal Fatawuri Syamsuddin; Hamzah Pagarra; Faidah Yusuf (KARYA: Journal of Educational Community Service, 2023)
This Community Service activity focuses on developing project modules to strengthen the profile of Pancasila students in junior high schools for junior high school teachers in Barru Regency. The main objectives of this service are: 1) improve the understanding and strengthening of the Pancasila learner profile of junior high school teachers; 2) develop innovative and effective project modules to support the achievement of goals; 3) improve the competence of junior high school teachers in Barru Regency in integrating Pancasila values into daily learning. The method used in the implementation of the education and training activities on Strengthening the Profile of Pancasila Students is based on the Participatory Action Research (PAR) approach. This approach was chosen because it provides an opportunity for all parties involved, including teachers, students, and the surrounding community to participate in the process of developing the project module. Through the application of the Participatory Action Research (PAR) method, the results and discussion illustrate the collaboration between presenters, teachers/participants and learners in identifying, planning, implementing, and evaluating the education and training program. Teachers' active participation in the entire flow of the PAR method contributed significantly to the success of the program, ensuring that the solutions produced were relevant and integrated with the school context. The implementation of education and training is considered successful based on the achievement of the main objectives of the service, namely: 1) The average score increase reached 23 points, reflecting the effectiveness of understanding and strengthening the Pancasila learner profile of junior high school teachers; 2) Teacher participation in developing innovative and effective project modules is at an average level above 90% and: 3) Teacher responses to the implementation of education and training were very positive, with an average satisfaction scale above 4.